Elevated sympathetic activity, endothelial dysfunction, and late hypertension after repair of coarctation of the aorta. (15th September 2017) - Lee, Melissa G.Y.; Hemmes, Robyn A.; Mynard, Jonathan; Lambert, Elisabeth; Head, Geoffrey A.; Cheung, Michael M.H.; Konstantinov, Igor E.; Brizard, Christian P.; Lambert, Gavin; d'Udekem, Yves
Abstract: Background: There is a high prevalence of late hypertension after coarctation repair. The relative contribution of elevated sympathetic tone and endothelial dysfunction to its development is unknown. This study aims to investigate the neural profile of coarctation patients including muscle sympathetic nerve activity testing to directly measure sympathetic nervous activity. Methods: Twenty-three patients aged ≥ 18 years with a coarctation repair underwent measurements of clinic and 24-h blood pressures, muscle sympathetic nerve activity, sympathetic and cardiac baroreflex functions, digital endothelial function, and ambulatory arterial stiffness index. Median age at repair was 1.2 months (interquartile range: 0–9 months). Patients were compared to 17 healthy matched controls. Results: After 26 ± 5 years, 6% (1/18) and 44% (8/18) suffered clinic hypertension and prehypertension, respectively. On 24-h blood pressure monitoring, 15% (3/20) and 20% (4/20) had hypertension and prehypertension, respectively. Coarctation patients had elevated muscle sympathetic nerve activity compared with controls (49.6 ± 24.9 vs. 29.9 ± 14.0 bursts/100 heartbeats, p = 0.02), dampened sympathetic baroreflex function (− 2.2 ± 2.1 vs. − 7.0 ± 5.6 bursts/100 heartbeats·mm·Hg − 1, p = 0.007), normal cardiac baroreflex function (41.9 ± 30.4 vs. 35.7 ± 21.1 ms·mm·Hg − 1, p = 0.6), endothelial dysfunction (pulse amplitude tonometry ratio: 0.39 ± 0.32 vs. 0.81 ± 0.50, p = 0.004), and increased ambulatory arterial stiffness index (0.46 ± 0.15 vs. 0.29 ± 0.17, p = 0.008). Conclusion: After coarctation repair patients have increased muscle sympathetic nerve activity, dampened sympathetic baroreflex response, endothelial dysfunction, and increased ambulatory arterial stiffness index, all of which may contribute to the development of late hypertension.